2007
DOI: 10.1186/1471-2474-8-6
|View full text |Cite
|
Sign up to set email alerts
|

The clinimetric qualities of patient-assessed instruments for measuring chronic ankle instability: A systematic review

Abstract: Background: The assessment of outcomes from the patient's perspective becomes more recognized in health care. Also in patients with chronic ankle instability, the degree of present impairments, disabilities and participation problems should be documented from the perspective of the patient. The decision about which patient-assessed instrument is most appropriate for clinical practice should be based upon systematic reviews. Only rating scales constructed for patients with acute ligament injuries were systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 41 publications
(56 reference statements)
4
146
0
2
Order By: Relevance
“…factor analysis and Cronbach's alpha), and alpha is between 0.70 and 0.90; ± doubtful method used (no factor analysis); -inadequate internal consistency (alpha \0.70); ? no information found on internal consistency'' [30,41,42].…”
Section: Description Of Synthesizing Methodsological Quality and Resultsmentioning
confidence: 99%
“…factor analysis and Cronbach's alpha), and alpha is between 0.70 and 0.90; ± doubtful method used (no factor analysis); -inadequate internal consistency (alpha \0.70); ? no information found on internal consistency'' [30,41,42].…”
Section: Description Of Synthesizing Methodsological Quality and Resultsmentioning
confidence: 99%
“…The FAAM has been demonstrated to be an appropriate, patient-oriented outcomes instrument for use in individuals with CAI. 11 Carcia et al 7 similarly identified group differences in FAAM scores between healthy athletes (100%  0% and 99%  4%) and those with CAI (88%  8% and 76%  13%). These results are also similar to those reported by Hale and Hertel, 18 who identified group differences on the Foot and Ankle Disability Index between recreational athletes with CAI and healthy subjects without a history of ankle injury.…”
Section: Stress Ultrasoundmentioning
confidence: 98%
“…115 The Foot and Ankle Outcome Score (FAOS) is a valid and reliable instrument. 115,336 The score is available in English, Swedish, Portuguese, Persian, Turkish, and Dutch.…”
Section: Introductionmentioning
confidence: 99%
“…115 The Foot and Ankle Outcome Score (FAOS) is a valid and reliable instrument. 115,336 The score is available in English, Swedish, Portuguese, Persian, Turkish, and Dutch. 5,207,297,336,356 Germany has the largest population of Europe but, to our knowledge, has no validated outcome score for general foot and ankle pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation